L'eau, enjeux politiques et théologiques, de Sumer à la Bible - Anthonioz, Stéphanie. (Vetus Testamentum, Supplements, 2009)
This book investigates a corpus of royal inscriptions and literary texts, with special emphasis on those that are mythological and biblical, stretching over several millennia from the early days of Sumer to the Biblical period, in order to determine the ways in which the concept of water was used, in particular the way it functions in the political and theological ideology of the time. Three literary motifs are the object of a careful study : the crossing of water, the flood and the water of abundance. Though their study shows diversity in evolution, transmission and reception, it appears that their function is common at the heart of the Mesopotamian political theology of royal mediation.